The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records - Bashir, Nawaz Haider; Du, Shi-Jie; Yue, Dan; Li, Qiang; Ma, Li (Zootaxa, 2019)
Four new species of genus Passaloecus Shuckard, (Crabronidae: Pemphredoninae: Pemphredonini) from China are described, namely P. bisulcatus Bashir & Ma, sp. nov., P. profundesulcatus Bashir & Ma, sp. nov., P. tuberangustus Bashir & Ma, sp. nov., and P. tuberculiformis Bashir & Ma, sp. nov. In addition, eight Palearctic species are reported, of which P. turanicus Gussakovskij and P. turionum Dahlbom are first records for China. A key to the species of Passaloecus from China is provided.